The impact of the rhizobia–legume symbiosis on host root system architecture. (27th April 2020) - Concha, Cristobal; Doerner, Peter
Abstract : Rhizobia improve legume N nutrition, and modulate other aspects of host nutrition and development. Symbiont impact on host resource allocation and root distribution, important for soil resource acquisition, is discussed. Abstract: Legumes form symbioses with rhizobia to fix N2 in root nodules to supplement their nitrogen (N) requirements. Many studies have shown how symbioses affect the shoot, but far less is understood about how they modify root development and root system architecture (RSA). RSA is the distribution of roots in space and over time. RSA reflects host resource allocation into below-ground organs and patterns of host resource foraging underpinning its resource acquisition capacity. Recent studies have revealed a more comprehensive relationship between hosts and symbionts: the latter can affect host resource acquisition for phosphate and iron, and the symbiont's production of plant growth regulators can enhance host resource flux and abundance. We review the current understanding of the effects of rhizobia–legume symbioses on legume root systems. We focus on resource acquisition and allocation within the host to conceptualize the effect of symbioses on RSA, and highlight opportunities for new directions of research.